2015
DOI: 10.3126/kumj.v12i3.13709
|View full text |Cite
|
Sign up to set email alerts
|

Movement Disability: Situations and Factors Influencing Access to Health Services in the Northeast of Thailand

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Trani et al found no difference in satisfaction with public health facilities in Afghanistan for people aged >5 years with and without disabilities [ 14 ]. In Thailand, a study by Wongkongdech et al found that 66% of people with physical impairment of all ages ranked their accessibility to health services at a moderate level (i.e., neither high nor low), taking in to account adequacy of health personnel, respect for rights and dignity, transport, service related aspects, personal factors and costs [ 62 ]. Finally, Badu et al found that 71% of people faced discrimination from health care providers [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Trani et al found no difference in satisfaction with public health facilities in Afghanistan for people aged >5 years with and without disabilities [ 14 ]. In Thailand, a study by Wongkongdech et al found that 66% of people with physical impairment of all ages ranked their accessibility to health services at a moderate level (i.e., neither high nor low), taking in to account adequacy of health personnel, respect for rights and dignity, transport, service related aspects, personal factors and costs [ 62 ]. Finally, Badu et al found that 71% of people faced discrimination from health care providers [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 36 studies, 10 were conducted in high income countries, including Australia [3740], United States [4144] and Canada [45, 46]. The remaining 26 studies originated from LMICs primarily from Ethiopia [4754], South Africa [5559], India [60, 61], Nepal [62, 63], Malawi [64], Mexico [65], Namibia [66], Pakistan [67], Tanzania [68], Thailand [69, 70] and Vietnam [71]. One article reported studies from four different African countries—Malawi, Namibia, South Africa and Sudan [72].…”
Section: Resultsmentioning
confidence: 99%
“…While most of the qualitative studies adopted generic qualitative approaches, five employed specific qualitative traditions including phenomenology [46, 54], grounded theory [55], ethnography [65] and participatory action research [71]. The 4 quantitative articles were cross-sectional studies [44, 59, 69] and a population-based household survey [72]. Twelve of the studies were aimed at rural health care access for PWDs in general.…”
Section: Resultsmentioning
confidence: 99%
“…When compared to peers without CP, children and adolescents with CP from LMICs had significantly poorer HRQoL, although discordance may be understated. A limitation of the included studies is that the majority of participants were accessed through rehabilitation and health services and may overstate well‐being compared to those who lack service access, as is common in LMICs . Additionally, five of the 16 studies excluded children with intellectual disability and may be a source of bias in results, although it is unclear how intellectual disability in LMICs interacts with HRQoL.…”
Section: Discussionmentioning
confidence: 99%